Sistem Informasi Pengaduan Siswa Berbasis Website Dengan Framework Laravel - Winda Uli Sari Manalu; Lukman Hakim; Cindi Wulandari (Journal of Information System Research (JOSH), 2023)
This student complaint system is a web-based system that helps Yadika Lubuklinggau Vocational High School students submit their complaints to the school. The challenge procedure is currently still manual. Students have to write complaints down on paper and then incorporate them into feedback, so this method is not efficient enough.Technology has become an important part of people's lives, especially in the world of education, this is triggered by the rapid development of technology.as technology advances.To overcome these problems, we need a website or technology that contains a collection of certain information pages that can be accessed easily by students anytime and anywhere so as not to interfere with the teaching and learning process. Created a system to design a web page system that can assist students in filing complaints. This program is based on PHP with the concept of MVC (Model View Controller), modeling of the proposed system, including diagramsuse case, scenariouse case, diagram activity, diagram sequence, diagram class, input and output plans. The design of this website uses the PHP programming language with the Laravel Framework programming language development method. Create a database with MySQL using XAMPP.The result of this research is to design a web-based complaint information system for Yadika Vocational High School students so that students can submit complaints outside of scheduled school hours. The benefits are too This website is accessed for online student complaint information systems.